Motorcycle rider conspicuity and crash related injury: case-control study. Issue 7444 (23rd January 2004) - Wells, Susan; Mullin, Bernadette; Norton, Robyn; Langley, John; Connor, Jennie; Jackson, Rod; Lay-Yee, Roy
Abstract: Objective To investigate whether the risk of motorcycle crash related injuries is associated with the conspicuity of the driver or vehicle. Design Population based case-control study. Setting Auckland region of New Zealand from February 1993 to February 1996. Participants 463 motorcycle drivers (cases) involved in crashes leading to hospital treatment or death; 1233 motorcycle drivers (controls) recruited from randomly selected roadside survey sites. Main outcome measures Estimates of relative risk of motorcycle crash related injury and population attributable risk associated with conspicuity measures, including the use of reflective or fluorescent clothing, headlight operation, and colour of helmet, clothing, and motorcycle. Results Crash related injuries occurred mainly in urban zones with 50 km/h speed limit (66%), during the day (63%), and in fine weather (72%). After adjustment for potential confounders, drivers wearing any reflective or fluorescent clothing had a 37% lower risk (multivariate odds ratio 0.63, 95% confidence interval 0.42 to 0.94) than other drivers. Compared with wearing a black helmet, use of a white helmet was associated with a 24% lower risk (multivariate odds ratio 0.76, 0.57 to 0.99). Self reported light coloured helmet versus dark coloured helmet was associated with a 19% lower risk. Three quarters of motorcycle riders had their headlight turned on during the day, and this was associated with a 27% lower risk (multivariate odds ratio 0.73, 0.53 to 1.00). No association occurred between risk and the frontal colour of drivers' clothing or motorcycle. If these odds ratios are unconfounded, the population attributable risks are 33% for wearing no reflective or fluorescent clothing, 18% for a non-white helmet, 11% for a dark coloured helmet, and 7% for no daytime headlight operation. Conclusions Low conspicuity may increase the risk of motorcycle crash related injury. Increasing the use of reflective or fluorescent clothing, white or light coloured helmets, and daytime headlights are simple, cheap interventions that could considerably reduce motorcycle crash related injury and death.